(untitled) (Annals of Medical Research, 2021)
Aim: To determine the reference values of normal ranges for liver, spleen and kidney dimensions for the preterm and term neonates Material and Methods: In this retrospective study, spleen, liver and kidney dimensions were evaluated in 222 healthy newborns with a gestation age of over 24 weeks at neonatal intensive care unit with sonography within the first week of life. Relationships of all dimensions with sex, gestational age, height and weight were statically analysed.Results: No statistically significant differences were found between the two sexes in any dimensions of the liver, spleen and kidney (p>0.05) . Gestational age, weight, and height were positively correlated with organ size (p0.01). Weight showed the best correlation of the measurements. Significant differences were observed between organ sizes in preterm and term infants (p=0.02)Conclusions: The reference values of spleen, liver and renal lengths and diagrams from this study may be useful in the sonographic evaluation of the preterm and term infants.